(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Polycystic ovary syndrome (PCOS) is a common condition affecting 4% to18% of women. It has been suggested that this condition occurs in as many as 4-10% ofwomen of reproductive age. PCOS is associated with significant reproductive morbidity,including infertility, abnormal uterine bleeding, miscarriage and other complications ofpregnancy. Method: This cross-sectional study was carried out in the Department of Obstetrics andGynaecology of Z.H. Sikder Women’s Medical College & Hospital, Dhaka from January,2013 to December, 2016 over a period of 4 years with the objective to find out various clinicalpresentations, endocrine status, the menstrual abnormalities and sonographic findings ofthe patients with PCOS. During the study period a total number of 1600 patients wereexamined for infertility in the Outpatient and in Inpatient Department. Out of these 1600infertility patients, 500 cases were found to have polycystic ovary syndrome. Detailedinformation about the patients were collected in a predesigned data collection sheet. Result: Out of 500 PCOS patients, 360 (72.0%) had primary sub-fertility and 140 (28.0%)had secondary sub-fertility. Age of the patients ranged between 25 and 35 years. Duration ofinfertility was between 5 to 18 years. Prevalence of menstrual disturbances was found in78.0 percent of PCOS patients, of which & 90 (18.0%) had amenorrhoea, 250 (50.0%) hadoligomenorrhoea, 50 (10.0%) had a heavy menstrual bleeding and 110 (22.0%) had normalmenstrual cycle. Among those patients, 210 (42.0%) were obese, 230 (46.0%) had normalBMI and 60 (12.0%) were under weight. Conclusion: The prevalence of PCOS in this study was 31.25% among infertility patients.Among them 72.0% had primary sub-fertility and 28.0% had secondary sub-fertility. Prevalenceof menstrual disturbances was found in 78.0% of PCOS patients, of which 18.0% hadamenorrhoea, 50.0% had oligomenorrhoea and 10.0% had heavy menstrual bleeding. Bangladesh J Obstet Gynaecol, 2018; Vol. 33(1) : 45-48